Preparation of Covalent-Ionically Cross-Linked UiO-66-NH2/Sulfonated Aromatic Composite Proton Exchange Membranes With Excellent Performance - Zheng, Penglun; Liu, Quanyi; Wang, Donghui; Li, Zekun; Meng, Yawei; Zheng, Yun (Frontiers in Chemistry, 2020)
Metal-organic frameworks (MOFs), as newly emerging filler materials for polyelectrolyte, show many compelling intrinsic features, such as variable structural designability and modifiability of proton conductivity. In this manuscript, UiO-66-NH2, a stable MOF with -NH2 functional groups in its ligands was selected to achieve a high performance sulfonated poly(arylene ether nitrile)s (SPENs)/UiO-66-NH2-x covalent-ionically cross-linked composite membrane. Simultaneously, the obtained composite membranes display excellent thermal stability and dimensional stability. The as-prepared SPEN/UiO-66-NH2-x cross-linked membranes exhibit higher proton conductivity than recast SPEN, which can be attributed to the construction of ionic clusters and well-connected ionic nanochannels along the interface between UiO-66-NH2-x and SPEN matrix via molecular interactions. Meanwhile, the methanol permeability of SPEN/UiO-66-NH2-x composite membrane has been effectively reduced due to the barrier effect of crosslinking and the addition of UiO-66-NH2-x. The SPEN/UiO-66-NH2-5 composite membrane has the highest selectivity of 6.42 105 S·s·cm-3, 14.3 times higher than that of Nafion 117. The preparation of cross-linked UiO-66-NH2/SPEN composite was facile，which provide a new strategy for preparing high performance proton exchange membrane.